The Elucidation of Africaness in Christianity Through Hierarchical Monotheism and Its Redefinition of Black Theology - Luyaluka, Kiatezua Lubanzadio (Black theology, 2017)
This paper is an elucidation of Afrocentricity in Christianity by means of a hierarchical monotheism, the theism of the Kongo religion, the Bukongo. The scientific validity of this theism, displayed through a cosmological argument, leads to the questioning of Eurocentric Christian monotheism, which can be argued does not conform to logic, nor to the perfection or the immutability of God. Next, the Bukongo is demonstrated to be the continuity of the solar religion of ancient Egypt and Sumer. Through the unity of the solar religion of Egypt, Sumer and Kongo and the southward migration of African peoples, the author shows that the different trends of African traditional religion (ATR) are only devolutions of the solar religion kept in the Bukongo. Having evidenced that early Christianity appertains to solar epistemology, the author arrives at the conclusion that it is itself a solar religion, one akin to ATR. This is confirmed by substantiating the presence in early Christianity of the main characteristics of ATR. Thus, this paper urges that far from a mere call for the enculturation and contextual adaptation of the Biblical message, Black theology must work to elucidate and exploit the solar nature of early Christianity to make clearer its connection with ATR.